Tools and terms for understanding illegal wildlife trade - Phelps, J.; Biggs, D.; Webb, E.L. (Wiley, 2016)
Illegal wildlife trade (IWT) is a global conservation issue that threatens thousands of species, including fish, fungi, medicinal plants, and charismatic mammals. Despite widespread recognition of the problem, debates on the science and policy of IWT generally concentrate on a few high‐profile species (eg rhinoceros, tigers, elephants) and often overlook or conflate complex IWT products, actors, networks, and contexts. A poor understanding of IWT is aggravated by the lack of systematic vocabulary and conceptual tools with which to analyze complex phenomena in a more structured way. We synthesize the available evidence on IWT across taxa and contexts into a typology‐based framework that considers (1) the diversity of wildlife products; (2) the roles of various actors involved with IWT, including harvesters, intermediaries, and consumers; and (3) common IWT network configurations. We propose ways in which these tools can inform structured analyses of IWT, to help ensure more nuanced, appropriate, targeted, and effective responses to illegal wildlife harvest, trade, and use.